Too Much in the Sun: Intentional Ambiguity in the Samson Narrative - Meshel, Naphtali S. (Hebrew studies, 2021)
This paper aims to expose a case of intentional ambiguity in the Samson narrative in Judges, and to demonstrate the literary and ideological value of the systematic ambiguity in the story of Samson's miraculous conception. In doing so, it adds one more item to a list of criteria that may be used to identify intentionality in ambiguous formulations - a criterion termed "hypergrammaticality."